The infrared excess emission from nearby Gaia DR2 M dwarfs. Issue 2 (24th August 2021) - Sgro, Lauren A; Song, Inseok
ABSTRACT: We use Gaia DR2 data to search for M dwarfs with infrared (IR) excess, within 100 pc. By cross-matching Gaia with AllWISE and 2MASS catalogues, we select a subset of K/M dwarfs with reliable photometric data in both the optical and near-to-mid IR. Using our SED fitting pipeline, we determine a photospheric model for each star and determine its significance of excess (SOE) in WISE passbands W 3 and W 4, which is used to classify potential IR excess. Through exhaustive vetting procedures, we present 37 new late-type IR-excess candidates, most of them M dwarfs, along with analyses of 12 previously known IR-excess stars. We group our candidates into two categories based on their SOE and likelihood of contamination. We also perform an isochronal age analysis as well as a moving group membership analysis, and discover six potential moving group members belonging to β Pictoris, Argus, Carina, Columba, and Tucana/Horologium Moving Groups. We conclude with a discussion of the nature of IR excess around late-type stars.